PERTUMBUHAN STEK TANAMAN LADA (Piper nigrum Linn) PADA KOMPOSISI MEDIA TUMBUH DAN DOSIS AIR KELAPA YANG BERBEDA - Aldi, Aldi; Muhardi, Muhardi; Lasmini, Sri Anjar (AGROTEKBIS, 2017)
This experiment aimed to determine the best growing media composition and coconut water in stimulating the growth of pepper plant cuttings. It used a two factorial randomized block design. The first factor was various proportions of media compositions of manure, sand and top soil i.e. 1:4:12; 1:4:6; and 1: 4:4. The second factor was different rates of coconut water i.e. A0           (no coconut water added), A1 (40 cc), A2 (80 cc), and A3 (120 cc). There were 12 combination treatments and each was replicated three times with each treatment consisting of three plants. Parameter observed included shoot length, leaf number, leaf area size, root length, and fresh root weight. The research results showed that there was no significant interaction effect between         the media composition and the coconut water on the shoot length at 45 days after planting (DAP), 60 DAP, and 90 DAP but it was significant at 75 DAP. The interaction effect was also significant on the leaf number at 60 DAP. Only the coconut water had significant effect on the total leaf area size, the root length, and the fresh weight. The stimulation of the pepper cutting growth was best under the 120 cc coconut water treatment per week and the sand, manure and top soil proportion of 1:4:4 treatment. Key Words : Coconut water, pepper cuttings, and planting media